If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 2)(2x + 5) = 0 Reorder the terms: (2 + x)(2x + 5) = 0 Reorder the terms: (2 + x)(5 + 2x) = 0 Multiply (2 + x) * (5 + 2x) (2(5 + 2x) + x(5 + 2x)) = 0 ((5 * 2 + 2x * 2) + x(5 + 2x)) = 0 ((10 + 4x) + x(5 + 2x)) = 0 (10 + 4x + (5 * x + 2x * x)) = 0 (10 + 4x + (5x + 2x2)) = 0 Combine like terms: 4x + 5x = 9x (10 + 9x + 2x2) = 0 Solving 10 + 9x + 2x2 = 0 Solving for variable 'x'. Factor a trinomial. (5 + 2x)(2 + x) = 0Subproblem 1
Set the factor '(5 + 2x)' equal to zero and attempt to solve: Simplifying 5 + 2x = 0 Solving 5 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 2x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + 2x = 0 + -5 2x = 0 + -5 Combine like terms: 0 + -5 = -5 2x = -5 Divide each side by '2'. x = -2.5 Simplifying x = -2.5Subproblem 2
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Solution
x = {-2.5, -2}
| (x-4)(x+6)+8=x(x+1)-13 | | x+3-9=0 | | -7x=49x^2 | | lx-3l-9=0 | | lx-3l+6=15 | | h+12=6 | | (4x-10)+x=90 | | -2g+-10=6 | | .8+.25x-.333=.75x | | -2 g+ -10= 6 | | y=0.2154x+15.85 | | 7x+3=3x-3 | | y=2154x+15.85 | | x=2(3.14)25+2(3.14)5(12) | | x-(8-3)=(3)-11 | | 2x*2=18 | | y+2x^2=5-2x | | 2.66+3n=0.80n+18 | | 32x^2y+44xy-40y= | | -12p-(+8)=40 | | 2.66+3n=0.8n+18 | | 7a-(3a-2)=18 | | 11m-23=12m+58 | | 34.1=-3.1(4y+5) | | 13AB-26A= | | -65=-13y | | 4x+9=43 | | 3.4(2x+5)=-23.8 | | 28y^2-88y^2+12y= | | 10y^2+34y-24= | | 3c^2+10c-8=0 | | 5a^2+8ab+3b^2= |